Late Quaternary sedimentation and tectonics in the submarine Sarkoy Canyon, western Marmara Sea (Turkey) - Ergin, M.; Uluadam, E.; Sarikavak, K.; Keskin, S.; Gokasan, E.; Tur, H. (GEOLOGICAL SOC PUBLISHING HOUSE, 2007)
Influences of tectonics and late Quaternary sea-level changes on sedimentation in the submarine Sarkoy Canyon, western Marmara Sea (Turkey) were investigated using a total of 37 seismic reflection profiles and 12 gravity sediment cores (with 63-435 cm thicknesses). which C-14 were collected at water depths ranging from 62 to 245 m. C-14 ages of base sections in three cores (11.585, 11.845 and 24.915 ka BP) and upward fining of grain size in the cores suggest that these sediments must have been deposited since the sea-level lowstand at about 12 ka BP, when the conditions in the Marmara Sea began to change from lacustrine to the present marine phase. With some exceptions, siliciclastic mud (silt + clay > 90%) with low carbonate contents (< 15% CaCO3) is the dominant sediment type covering the floor of the canyon. The high organic carbon contents (1-2%) with slight downcore-increasing tendencies reflect higher primary organic productivities towards the early Holocene. Faults, sedimentation deformation structures, and submarine slides or stumps observed on seismic profiles, varying elevations of dated lowstand palaeoshores and low water contents (19-25%) of sediments at some sites together strongly indicate the important effect of neotectonics on sedimentation in this canyon. On the seismic profiles at least four stratigraphic units were recognized overlying the pre-Miocene basement. which indicate not only the effects of faulting and folding but also changing conditions and related depositional environments in and around the canyon. Geological evolution and thus the sea-floor morphology of the Sarkoy Canyon is controlled by both regional Plio-Quaternary tectonics and global Quaternary sea-level changes.
Keywords: NORTH ANATOLIAN FAULT; BLACK-SEA; ORGANIC-CARBON; NEOTECTONIC STRUCTURES; SAPROPELIC LAYERS; LEVEL CHANGES; AEGEAN SEA; EVOLUTION; SLIP; REGION; Geochemistry & Geophysics; Geology